Acesso e uso da informação em sistemas de bibliotecas universitárias federais para usuários da educação a distância (EaD) - Maria Elizabeth de Oliveira da Costa (2020)
Distance Education contributes greatly to the universalization and democratization of knowledge in society. In this context, regarding the characteristics and purposes of such mode of learning, it is seen not as a new educational approach, but as a way of inserting individuals into a society. Nevertheless, problems may interfere in the management of information resources in relation to the availability, access, and use of such resources for users of Distance Education. This research focuses on these matters. This study encompasses federal universities in the five regions of Brazil, with a focus on Library Systems, on Distance Education Centers, and on students from the following institutions: Federal University of Minas Gerais and Federal University of Ouro Preto (Southeast), University of Brasília (Center-West), Federal University of Amazonas (North), Federal University of Rio Grande do Sul (South), and Federal Rural University of Pernambuco (Northeast). The general objective is to describe the status of Library Systems and their integration with Distance Education in Brazil, thus identifying critical aspects and/or contributions of University Libraries in arrangements related to distance learning, especially the guidelines and support given to users. Specific objectives include: identifying whether or not Systems have units or sectors responsible for supporting students in distance learning; identifying whether or not these systems offer any services or products for students, and whether or not they have worked in partnership with the Distance Learning Support Center; whether or not the Systems interact with the Distance Learning Hub Libraries; and whether or not distance learning students are aware of and/or use technical-scientific materials, whether or not they have access to them, how they obtain informational support, and whether or not they are satisfied with what is offered; and suggesting directions toward a management plan for University Libraries regarding the availability, access, and use of information resources. This research uses three methods of data collection: documentary research, interviews with directors of Library Systems and Distance Education Support Centers, and web-survey of users. The results indicate that distance learning has been appreciated and valued, guaranteeing universal access to education. Challenges were found, most of them associated with the need to publicize services and the lack of human resources and infrastructure that guarantees equal access, especially for students who use the Hubs. This reinforces the importance of integrating involved institutions (Libraries, Support Centers, and Hub Libraries). This study suggests that institutions must be aware of this new reality. Librarians need to act as information mediators in conjunction with the institution’s Support Centers and with Hub Libraries, promoting actions, services, and products so that support for technical and scientific information reaches the distance learning community. Equality in these services is stressed, as distance learning aims at making education reach the most remote places in the country, benefiting students who are away from large urban centers.